2020
DOI: 10.1101/2020.07.09.195362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous social communication in laboratory mice - placing ultrasonic vocalizations in their behavioral context

Abstract: AbstractIn their natural habitat, mice interact and communicate to regulate major functions, such as reproduction, group coordination, and protection. Nevertheless, little is currently known about their spontaneous emission of ultrasonic vocalizations (USVs), despite their broad use as a phenotypic marker in mouse models of neuropsychiatric disorders. Here, we investigated mouse spontaneous communication by coupling automatic recording, segmentation, and analysis of USVs to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 78 publications
2
35
0
Order By: Relevance
“…In comparison to their normal controls, many Dlx5/6 VgatCre and Dlx5/6 VgaCre/+ mice emit a higher number of longer "complex" calls often not separated by any interruption. These long-modulated USVs are emitted prevalently when mice are engaged in socially-intense behaviours and more rarely during isolated behaviour (Ey, et al 2020). Therefore, the high-vocalization profile of Dlx5/6 VgatCre mice is predictive of an enhanced social behaviour and is in line with our finding of an increase in dynamic socialization of highvocalizing individuals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In comparison to their normal controls, many Dlx5/6 VgatCre and Dlx5/6 VgaCre/+ mice emit a higher number of longer "complex" calls often not separated by any interruption. These long-modulated USVs are emitted prevalently when mice are engaged in socially-intense behaviours and more rarely during isolated behaviour (Ey, et al 2020). Therefore, the high-vocalization profile of Dlx5/6 VgatCre mice is predictive of an enhanced social behaviour and is in line with our finding of an increase in dynamic socialization of highvocalizing individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of the specific types of calls emitted by each animal showed that high-vocalizing animals presented a significant increase in the number of complex vocalizations ("modulated + complex" according to (Ey, et al 2013)) which are the longer vocalization types emitted by mice and can last up to 0.15ms (Figure 3 B). Complex vocalizations have been recently associated to more social behaviours (Ey, et al 2020). Therefore, in this experimental paradigm, designed to detect social vocalization, we observed a new partially-penetrant phenotype characterized by an increase in the number calls, and differences in vocal repertoire and "prosody" (Lahvis, et al 2011).…”
Section: Dlx5/6 Expression In Gabaergic Neurons Affects Mouse Social mentioning
confidence: 97%
See 1 more Smart Citation
“…Ey et al revealed that mice used call types in a context-specific manner in same-sex pairs. Interestingly, female pairs emitted more USVs than males when encountering the partner female [10]. Collectively, female mice have the potential to emit USVs, and the emission of USVs also reflects a high level of excitement in social interactions across different contexts [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, female pairs emitted more USVs than males when encountering the partner female [10]. Collectively, female mice have the potential to emit USVs, and the emission of USVs also reflects a high level of excitement in social interactions across different contexts [10,11]. In the context of male and female sexual interactions in standard experimental settings, male mice are more excited and emit more USVs than females [12,13].…”
Section: Introductionmentioning
confidence: 97%